Pembinaan Prestasi Ikatan Pencak Silat Indonesia (IPSI) di Kabupaten Wonosobo Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of the study was to determine the implementation of achievement development, training programs, organization, knowing the role of coaches, knowing the condition of athletes, knowing IPSI facilities and infrastructure in Wonosobo Regency. The study used a qualitative descriptive approach. The subject of this research is IPSI Wonosobo Regency which consists of, 2 IPSI Management Wonosobo Regency, 1 coach and 4 athletes. Data collection was taken by the method of observation, interviews and documentation. The results of the study show that the achievement development carried out by IPSI in Wonosobo Regency has been going well but there are obstacles in the facilities and infrastructure section. The IPSI organization of Wonosobo Regency has been running well and has been in accordance with the functions of each administrator. The training program owned by IPSI Wonosobo Regency is well planned and adjusted based on the character of the athlete. From the results of the study, it can be concluded that the IPSI Achievement Development in Wonosobo Regency has been going well but is constrained by the facilities and infrastructure for other aspects. by looking at the aspects of mass production, breeding, achievement, organization, training programs, human resources, and funding. Suggestions for research is that achievement development can be carried out continuously and continuously.